UPDATING PERATURAN PAJAK GUNA MENINGKATKAN EMPLOYABILITY SKILLS - Makaryanawati, Makaryanawati; Putri, Sheila Febriani; Ermayda, Ria Zulkha; Febriyanti, Syaila Putri; Indah Sari, Vivid Nur (Jurnal Likhitaprajna, 2023)
Tax regulations always undergo many changes considering that taxes are the most important state revenue. Changes in these regulations have an impact on alumni who work in the field of taxation. There is a gap between alumni's understanding of taxation and tax regulations that have changed, so it is necessary to educate them about taxation in the form of training. This activity aims to provide provision related to the latest taxation material for alumni so that it is hoped that alumni can be accepted in the world of work. The implementation of activities is carried out through four stages, including the data analysis stage, socialization of activities, study and formulation of activities, implementation of activities, as well as providing feedback to participants and evaluation of activities. This service activity in the form of tax training for alumni of the Faculty of Economics and Business has been carried out well. The result of this training activity is an increase in alumni's understanding of changes in tax regulations for VAT and income tax and solutions in dealing with various tax-related problems.